(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study discussed about the awareness and utilisation and SWAYAM portal among Engineering Students of Sri Venkateswara University, Tirupati. The questionnaire method is used to gather information from participants. An online questionnaire was designed for this purpose and circulated to 82 students. 78 responses received out of 82 total. The overall user response rate 95.%. The information is presented in the form of tables and evaluated using a basic measurement process. The results found that all are aware and utilising the portal and 71(91.02%) respondents agreed that there is an impact of SWAYAM on their study and research.